Jaipur Literature Festival, the Gendered Literary Field, and the MeToo Movement in India - Das, Arpita (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
As the literary field in India begins to become more complex, layered and diverse in terms of its gender representation despite the stubborn persistence of many aspects of its “tradition” male bastion character, the most celebrated and successful literary festival in the country emerges as a microcosmic manifestation of this tussle for power. Based on an autoethnographic account of the literary festival over eight editions and a close narrative of the sessions in its 2018 and 2019 editions along with a look at how these editions were reported in the media, and placing them within the frame of scholarship researching literary festivals as representations or fragments of “public culture”, this article looks at gender representation at the Jaipur Literature Festival in the immediate aftermath of the two waves of the MeToo Movement in India.